Journey through 1971 : my story - Huq, Farida (Dhaka : Academic Press and Publishers Limited, 2004)
Autobiographical reminiscences about her youth of a 20th century author from Bangladesh; includes reminiscences of her days through 1971 Bangladesh liberation war while staying in Pakistan.
Keywords: Huq, Farida -- Childhood and youth; Authors, Bangladeshi -- 20th century -- Biography; Bangladesh -- History -- Revolution, 1971 -- Personal narratives